Phase transformations and vibrational properties of hybrid organic–inorganic perovskite MAPbI3 bulk at high pressure - Ardimas; Teerachote Pakornchote; Wiwittawin Sukmas; Sojiphong Chatraphorn; Stewart J. Clark; Thiti Bovornratanaraks (Scientific Reports, 2023)
Abstract The structural stability and internal properties of hybrid organic–inorganic perovskites (HOIPs) have been widely investigated over the past few years. The interplay between organic cations and inorganic framework is one of the prominent features. Herein we report the evolution of Raman modes under pressure in the hybrid organic–inorganic perovskite MAPbI $$_3$$ 3 by combining the experimental approach with the first-principles calculations. A bulk MAPbI $$_3$$ 3 single crystal was synthesized via inverse temperature crystallization (ITC) technique and characterized by Raman spectroscopy, while the diamond anvil cells (DACs) was employed to compress the sample. The classification and behaviours of their Raman modes are presented. At ambient pressure, the vibrations of inorganic PbI $$_6$$ 6 octahedra and organic MA dominate at a low-frequency range (60–760 cm $$^{-1}$$ - 1 ) and a fingerprint range (900–1500 cm $$^{-1}$$ - 1 ), respectively. The applied pressure exhibits two significant changes in the Raman spectrum and indicates of phase transition. The results obtained from both experiment and calculations of the second phase at 3.26 GPa reveal that the internal vibration intensity of the PbI $$_6$$ 6 octahedra (< 110 cm $$^{-1}$$ - 1 ) reduces as absences of MA libration (150–270 cm $$^{-1}$$ - 1 ) and internal vibration of MA (450–750 cm $$^{-1}$$ - 1 ). Furthermore, the hydrogen interactions around 1300 cm $$^{-1}$$ - 1 remain strong high pressure up to 5.34 GPa.